Childhood and Adolescent Pesticide Exposure and Breast Cancer Risk. Issue 3 (May 2016) - Niehoff, Nicole M.; Nichols, Hazel B.; White, Alexandra J.; Parks, Christine G.; D'Aloisio, Aimee A.; Sandler, Dale P.
Abstract : Background: To date, epidemiologic studies have not strongly supported an association between pesticide exposure and breast cancer. However, few previous studies had the ability to assess specific time periods of exposure. Studies that relied on adult serum levels of metabolites of organochlorine pesticides may not accurately reflect exposure during developmental periods. Furthermore, exposure assessment often occurred after diagnosis and key tumor characteristics, such as hormone receptor status, have rarely been available to evaluate tumor subtype-specific associations. We examined the association between pesticide exposure during childhood and adolescence and breast cancer risk in the prospective Sister Study cohort (N = 50, 884 women) to assess this relation by tumor subtype. Methods: During an average 5-year follow-up, 2, 134 incident invasive and in situ breast cancer diagnoses were identified. Residential and farm exposure to pesticides were self-reported at study enrollment during standardized interviews. Multivariable hazard ratios and 95% confidence intervals for breast cancer risk were calculated with Cox proportional hazards regression. Results: HRs were near null for the association between childhood/adolescent pesticide exposure and breast cancer risk overall or among ER+/PR+ invasive tumors. However, among women who were ages 0–18 before the ban of dichlordiphenyltrichloroethane in the US, exposure to fogger trucks or planes was associated with a hazard ratio = 1.3 for premenopausal breast cancer (95% confidence interval: 0.92, 1.7). Conclusion: These findings do not support an overall association between childhood and adolescent pesticide exposure and breast cancer risk. However, modest increases in breast cancer risk were associated with acute events in a subgroup of young women.